Seismic Isolation Performance Evaluation for a Class of Inerter-Based Low-Complexity Isolators - Fei Cao; Michael Z. Q. Chen; Yinlong Hu (Shock and Vibration)
In this paper, the seismic base isolation problem for all low-complexity networks containing one inerter, one spring, and one damper is studied based on a multi-degree-of-freedom model. The analytical solutions for the H2 performance optimization are derived, and the traditional tuned mass damper (TMD) is employed for comparison. Extensive numerical simulations are performed to verify the effectiveness of the obtained results. The results show that for different seismic wave excitations, some isolators are better than TMD in controlling the displacement of the main structure. Moreover, with the increase of the TMD mass ratio, the isolation performances of the inerter-based isolators are increasingly better than that of TMD.